Marxist Philosophy and the Themes of Materialism and Capitalism in Dickens’s Hard Times - Dian Misesani; Ali Mustofa (Universitas Ahmad Dahlan, 2022)
This study aimed to analyze the themes of materialism and capitalism in one of Charles Dickens’s novels entitled Hard Times, which is thick with industrial capitalism. Specifically, it aims at (1) finding the themes of materialism and capitalism by coding themes in terms of words and/or phrases frequency in Dickens’s Hard Times and (2) analyzing and interpreting the theme of materialism and capitalism exposure through the characters’ discursive, setting, and narration in the novel. This research was included in a thematic study that employed a quantitative content analysis. The findings showed that the themes of this novel were materialism and capitalism. Some of the most frequently used words are ‘fact’, ‘money’, and ‘capital’, representing materialism and capitalism. The story of this novel reflects the vice or negative society that happened in England during the 18-19th century as the impacts of industrial capitalism and materialism.